Clinical study of management and outcomes in patients with degenerative cervical myelopathy treated with anterior cervical discectomy and fusion: an institutional experience and review of literature - Tushar Soni; Divyang Patel; Tejas Chotai; Shreyansh Patel; Manas Ranjan Deo (Ukrainian Neurosurgical Journal)
This prospective observational study was done to evaluate the outcomes and management of patients with degenerative cervical myelopathy (DCM) treated with anterior cervical discectomy and fusion (ACDF). Materials and methods: Our study included 80 patients with DCM admitted to a neurosurgical department between August 2013 and February 2023. Patients underwent ACDF surgery for single- or multi-level spinal canal stenosis. Demographic data, clinical features, and neurological examinations including assessments of limb power using the Medical Research Council Scale, sensory system function, and sphincter disturbance pre- and post-operatively were assessed. Pre- and post-operative neurological function was evaluated using the Nurick score, while post-operative outcomes were assessed using the Odom's criteria. The study population consisted mainly of males aged 51-60 years. Myelopathy was the most frequent presentation, with C5-C6 level being the most common level of fusion. Results: ACDF surgery significantly improved neurological function, as evidenced by reduced pre-operative weakness and sensory dysfunction, and increased post-operative muscle strength. Minimal postoperative complications were observed. Conclusions: These findings align with previous research, demonstrating ACDF as a safe and effective procedure for improving neurological function and quality of life in DCM patients. Limitations include sample size and study design, necessitating further research.